PENGARUH IKLIM ORGANISASI TERHADAP MOTIVASI KERJA PEGAWAI DI KANTOR CAMAT AMANDRAYA KABUPATEN NIAS SELATAN - Yohana Destian Hia (Universitas Nias Raya, 2023)
The purpose of this study was to determine the influence of organizational climate on work motivation of employees at Amandraya Sub-district Office, South Nias Regency. The type of research used is a quantitative type of causal nature. The source of the data was from employees, with the population and sample in this study being 31 respondents. Data collection techniques are research instruments or questionnaires. The data analysis method used is a simple linear regression analysis. The results of this study showed that the counting value of 4,963 >ttabel value 1,549. This research can be concluded that there is influence of organizational climate on the work motivation of employees at the Amandraya Sub-district Office, South Nias Regency. There are suggestion of this study numer (1) The work motivation of employees of the Amandraya Sub-district office needs to be improved, among others, through improving organizational climate conditions that further stimulate employee morale. (2) The leadership of the organization needs to provide good motivation for employees by providing the facilities needed in carrying out work such as vehicles, computers so that the work can run well.